Snowpack disrupts relationship between young water fraction and isotope amplitude ratio; approximately one fifth of mountain streamflow less than one year old. Issue 25 (8th October 2020) - Campbell, Éowyn M. S.; Pavlovskii, Igor; Ryan, M. Cathryn
Abstract: Previous "fraction of young water" ( F yw ) estimates based on relative annual isotopic amplitudes in precipitation ( A p ) and streamflow ( A s ) produced low F yw values in mountain catchments, which is contrary to extensive research that reports rapid water transmission in mountains. This study investigated this discrepancy by testing the effect of snow accumulation on the model that underpins the F yw method. A Monte‐Carlo analysis of simulations for 20, 000 randomly‐generated catchment model configurations used 10 years of precipitation inputs for the Upper Elbow River catchment in the Rocky Mountains (Alberta, Canada) to model discharge with and without snowpack storage of winter precipitation. Neither direct nor modified precipitation input produced a 1:1 relationship between A s / A p and F yw, undermining the applicability of the original F yw method in mountain watersheds with large seasonal snow accumulation. With snowpack‐modified input a given A s / A p ratio corresponds to a range of F yw values, which can still provide semi‐quantitative information. In the small (435 km 2 ) Elbow River catchment a F yw range of 7–23% supports previous findings of rapid transmission in mountain catchments. Further analysis showed that the improved discharge prediction (Nash–Sutcliffe efficiency > 0.9) correlates with higher F yw values and demonstrated that the interannual shifts in δ 18 O can be used to estimate of new water (<1 year) fraction in winter streamflow, and the estimate of 20% for the Elbow River further supports rapid transmission in mountain catchments. Abstract : Snowpack disrupts seasonal cycles of isotopic variability, preventing accurate estimation of F yw in catchments with overwinter snowpack Monte‐Carlo simulations produce a range of possible F yw for a given measured A r / A p, and together with an independent estimate, show that ~1/5 of streamflow in the study catchment is less than 1 year old.